PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA DRIVE INCARWASH DI JAKARTA - Siska Yunanti; Aries Jaya Zay; Mitri Nelsi (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of compensation and work discipline on employee performance at Drive In Carwash West Jakarta, both partially and simultaneously. This type of research is a quantitative approach. The population of this study was all employees of Drive In Carwash West Jakarta as many as 61 employees and the determination of the sample used saturated samples where the entire population was sampled, so that the sample of this study was 61 respondents. Data were collected through questionnaires filled out by employees and analyzed using simple linear regression and multiple linear regression with the help of the SPSS version 26 program. The results of this study showed that partially compensation had a significant effect on employee performance with the regression equation Y = 19.458 + 0.533X1. The correlation coefficient value of 0.522 means that both variables have a moderate level of influence with a determination coefficient of 26.8%. Hypothesis testing obtained t count> t table or (3.042> 1.688), this is reinforced by a significant probability of 0.000 <0.05. Partially work discipline has a significant effect on employee performance with the regression equation Y = 29.735 + 0.289X2. The correlation coefficient value of 0.406 means that both variables have a moderate level of influence with a determination coefficient of 26.8%. Hypothesis testing obtained t count> t table or (1.848> 1.688), this is reinforced by a significant probability of 0.000 <0.05, and simultaneously Compensation and Work Discipline have a significant effect on Employee Performance with the regression equation Y = 17.904 + 0.413X1 + 0.162X2. The correlation coefficient value obtained is 0.518, meaning that the independent variable with the dependent variable has a moderate level of influence with a determination coefficient or simultaneous influence of 26.8% while the remaining 73.2% is influenced by other factors. Hypothesis testing obtained F count> F table or (11.721> 3.14), this is also reinforced by a significant probability of 0.000 <0.05.